Brief history of lethality in the exercise of police activity in the State of Pará, Amazonia-Brazil (Research, Society and Development, 2020)
The study aims to analyze the frequent phenomenon of lethality resulting from police intervention in the State of Pará, Brazil. The technique of descriptive statistics is used, with a quantitative focus of the data, from a census of the cases registered in the period from 2011 to 2016, in the State of Pará. The police data were obtained from the Civil Police of the State of Pará. The results obtained indicate the incidence with an upward trend of deaths resulting from police intervention, mainly in the Metropolitan Region of Belém, capital of the State. Therefore, there is a for frequent interaction between society and police as a means of effective control of police activity, ensuring respect for human rights.